Methionine peptide formation under primordial earth conditions. - Li, F; Fitz, D; Fraser, D; Rode, B (2008)
According to recent research on the origin of life it seems more and more likely that amino acids and peptides were among the first biomolecules formed on earth and that a peptide/protein world was thus a key starting point in evolution towards life. Salt-induced Peptide Formation (SIPF) has repeatedly been shown to be the most universal and plausible peptide-forming reaction currently known under prebiotic conditions and forms peptides from amino acids with the help of copper ions and sodium chloride. In this paper we present experimental results for salt-induced peptide formation from methionine. This is the first time that a sulphur-containing amino acid was investigated in this reaction. The possible catalytic effects of glycine and L-histidine in this reaction were also investigated and a possible distinction between the L- and D-forms of methionine was studied as well.